MANFAAT TANAMAN SAGU (Metroxylon sp) DALAM PENYEDIAAN PANGAN DAN DALAM PENGENDALIAN KUALITAS LINGKUNGAN - Bambang Hariyanto (Jurnal Teknologi Lingkungan, 2011)
Sago plants is a source of carbohydrates that can be used as a source of food. With the extruder technology, sago can be made noodles. The purpose of this study is to know the utilization of sago as a provider of food and protecting the environment. Organoleptic testing sago noodles and wheat noodles to the panelists gave results not significantly different. The noodles of sago have a high resistant starch and useful for health. To make use of sago in the manufacture of noodles in the framework of implementation of the Gouverment Regulation (Per Pres) No. 22 th 2009 the need for socialization and support for raw material supplies through sago plantations. When the sago plant is developed it will be beneficial to the absorption of carbon dioxide andmaintain the sago air. Sago palm can produced 20 tonnes karbohidrat / ha. Besides sago plants will be able to keep the water around it. Sago leaf has the ability to absorbcarbon dioxide (CO2) emissions by 240 tons CO2/ha/th.